Self-regulation of wealth - Schink, Gregory H.G. (Kansas State University, 2018)
The purpose of this study was to determine the influence of self-regulation on positive financial behaviors and bankruptcy filings of high net worth individuals. The implications are directed toward various groups and factions of high net worth individuals as populations of interest. The basic premise of self-regulation of behavior theory is that human action is driven by attainment of goals and the degrees and forms of behavior expressed by an individual can be quantified by specific personality characteristics which affect both the response to, and velocity toward, those goals (Carver & Scheier, 1998). A survey administered to high net worth individuals (i.e., net worth of $1 million or greater) with a oversampling of high net worth individuals who have filed bankruptcy focused on self-reporting personality measures key to the self-regulation of behavior theory, such as optimism-pessimism and appetitive motives. By utilizing data gathered from high net worth individuals, a t test was used to examine mean differences in the personality characteristics of high net worth individuals who have filed bankruptcy and high net worth individuals who have not filed bankruptcy. The debt-to-income and debt-to-assets ratios were utilized as the dependent variables in an OLS regression analysis to analyze if any of the variables of interest significantly influenced the debt-to-income ratio, or DTI, or debt-to-assets ratio, or debt-ratio. This was followed by a logistic regression analysis predicting the odds of a bankruptcy filing based on the variables of interest. Potential differences in personality and behavior may explain wealth management issues that exist between high net worth individuals who have filed bankruptcy and high net worth individuals who have not filed bankruptcy.
Keywords: self-regulation; wealth; bankruptcy